НАРУШЕНИЕ КОГНИТИВНЫХ ФУНКЦИЙ: АКТУАЛЬНОСТЬ ПРОБЛЕМЫ, ФАКТОРЫ РИСКА, ВОЗМОЖНОСТИ ПРОФИЛАКТИКИ И ЛЕЧЕНИЯ - Л. Г. Гимоян; Г. Г. Силванян (Архивъ внутренней медицины)
Cognitive dysfunction draws more and more attention of doctors and researchers. The article contains a detailed analysis of risk factors, clinical features and possibilities for cognitive rehabilitation. Neuroprotective therapy in conjunction with adequate correction of homeostasis and hemodynamic is of high practical importance. The suggested methodology directed towards improvement of cholinergic transmission with the use of Mildronat, Actovegin and Ceraxon is rather efficient and can be recommended as medicine of choice not only as cognitive preserved but also as cognitive restoring medicines.